Centers of the scientific movement in Iraq (From the middle of the fourth century AH to the middle of the fifth century AH) - عبيدة, سام (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Iraq witnessed cultural and intellectual development in the middle of the fourth century AH until the Seljuks took control of it. During that period, centers and places for learning and disseminating diverse culture and sciences spread throughout Iraq. Among its most important centers were Baghdad, Mosul, Wasit, Kufa, and Basra. They spread in several places of Places of worship, monasteries, mosques, councils of scholars, public and private scientific circles, and even in the private homes of scholars, which made teachers and learners flock to Iraq in large numbers. These centers were praised and sung by the poets of that era because of the important role they played in advancing the scientific movement and were an example of religious tolerance in Iraq at that time. The most important of these centers are Al-Mansour Mosque, Buratha Mosque, and Al-Mahdi Mosque. And Dar Ilm Sabur, and among the most important councils of scholars: the council of Abu Al-Hasan Ali bin Isa Al-Rummani 382 AH / 992 AD, the council of Sheikh Al-Mufid 413 AH / 1022 AD, the council of Ali bin Omar Abu Al-Hasan Al-Qazwini Al-Zahid 442 AH / 1050 AD, and the modified council of Abu Al-Faraj (Ahmad bin Muhammad) 415 AH / 1024 AD , Council of Abu Jaafar Al-Samnani, Ahmed bin Muhammad, 444 AH / 1052 AD. Every member of Iraqi society, no matter how high he was at first, would go to the place that suited his intellectual, cultural, and religious inclinations, especially since religious and intellectual freedom was unleashed during that period.